Effect of Dietary Supplementation of Red Pepper and Black Pepper Powder on Feed Intake and Growth Performance of Broiler Chicken - Acharya, Rabin; Gautam, Manish; Pandey, Tek; Adhikari, Bishnu Prasad (International Journal of Applied Sciences and Biotechnology, 2025)
A series of experiments were conducted to investigate the effects of red pepper and black pepper powder supplementation on feed intake, feed conversion ratio, and growth performance in broiler chickens. Two-hundred-day-old Cobb 500 Strain broiler chickens were randomly divided into five treatments, each replicated four times, with 10 birds per replication from second week. The basal feed was supplemented with ground red pepper and black pepper in varying proportions: T1 (control); T2 (basal diet + 0.02% red pepper); T3 (basal diet + 0.02% black pepper); T4 (basal diet + 0.01% red pepper + 0.01% black pepper); and T5 (basal diet + 0.02% red pepper + 0.02% black pepper). The results indicated that T5 (0.02% red pepper + 0.02% black pepper) showed the best performance (p < 0.05) in all growth parameters, including final body weight, weekly feed intake, and feed conversion ratio. The study demonstrated that supplementing broiler chickens with 0.02% red pepper and 0.02% black pepper significantly improved growth performance metrics such as body weight, weight gain rate, and feed efficiency. In conclusion, the inclusion of 0.02% red pepper and 0.02% black pepper powder in the basal feed is a simple and effective strategy to enhance the overall growth performance of broiler chickens. Int. J. Appl. Sci. Biotechnol. Vol 13(1): 46-51.